A Novel Catecholopyrimidine Based Small Molecule PDE4B Inhibitor Suppresses Inflammatory Cytokines in Atopic Mice - Purushothaman, Baskaran; Arumugam, Parthasarathy; Song, Joon Myong (Frontiers in Pharmacology, 2018)
Degradation of cyclic adenosine mono phosphate (cAMP) by phosphodiesterase-4B (PDE-4B) in the inflammatory cells leads to elevated expression of inflammatory cytokines in inflammatory cells. Suppression of cytokines has proved to be beneficial in the treatment of atopic dermatitis (AD). Henceforth, application of PDE4B specific inhibitor to minimize the degradation of cAMP can yield better results in the treatment of AD. PDE4B specific inhibitor with a limited side effect is highly warranted. Herein, we synthesized a novel PDE4 inhibitor, compound 2 comprising catecholopyrimidine core functionalized with trifluoromethyl (–CF3) group. PDE4B inhibitory potential and specificity of novel compounds were evaluated by PDE inhibitor assay. In-vivo efficacy of the compounds was analyzed using DNCB-induced NC/Nga mice. IgE, CD4+ T-helper cell infiltration, and cytokine profiles were analyzed by ELISA and immunohistochemistry techniques. Toluidine blue staining was performed for mast cell count. PDE4 inhibitor assay confirmed that compound 2 specifically inhibits PDE4B. In-vivo analysis with DNCB-induced NC/Nga mice confirmed that compound 2 suppressed the levels of pro-inflammatory cytokines such as TNF-α, IL-4, IL-5, and IL-17. Furthermore, compound 2 significantly reduced the infiltrative CD4+ T-helper cells, mast cells and IgE levels in atopic tissue. The in-vitro and in-vivo data suggested that compound 2 specifically inhibit the PDE4B and the symptoms of the AD in atopic mice. Compound 2 might constitute a good candidate molecule for the treatment of AD.